MIGRATION ALS ERINNERUNGSORT? EIN INTERDISZIPLINÄRES THEMA UND SEINE IMPLIKATIONEN FÜR DAS FACH DEUTSCH ALS FREMDSPRACHE - Janachowska-Budych, Marta (Neofilolog, 2020)
The following article discusses the potentials of sites of memory of migration as a topic for teaching German as a foreign language, as they do not seem to have been thoroughly and systematically investigated or reflected upon so far. In the first part of the paper, the theoretical frames for combining the topic of migration with the concept of sites of memory are presented. In the second part, examples of ways of working with specific topics and media on sites of memory of migration in German as a foreign language classes are given and their possible potentials for supporting reflective cultural learning are examined.